2019
DOI: 10.1097/md.0000000000018405
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence of sleep disorders and behavioral and psychological symptoms of dementia in late-onset Alzheimer disease

Abstract: Alzheimer disease (AD) is the most common neurodegenerative brain disease that causes cognitive impairment in the elderly. Behavioral and psychological symptoms of dementia (BPSD), also known as neuropsychiatric symptoms, represent a heterogeneous group of non-cognitive symptoms and behaviors for AD patients. Sleep disorder is one closely-related psychiatric symptom of AD. In this cross-section study, we aimed to investigate the characteristics of sleep status and BPSD among AD patients in Eastern China and to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
26
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 45 publications
4
26
0
2
Order By: Relevance
“…(93/126) of cases were diagnosed with sleep disorders in our cohort of AD patients, which was supported by previous reports showing a significantly higher incidence of sleep disturbance in Alzheimer's disease patients compared to control population 12,37 .…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…(93/126) of cases were diagnosed with sleep disorders in our cohort of AD patients, which was supported by previous reports showing a significantly higher incidence of sleep disturbance in Alzheimer's disease patients compared to control population 12,37 .…”
Section: Discussionsupporting
confidence: 89%
“…These results were supported by a cross-section study showing an inverse correlation between sleep length and anxiety symptoms in Alzheimer's disease patients 39 and by a recent study from a Chinese cohort showing a close correlation between PSQI scores and depression in Alzheimer's disease patients 37 . So far there is a paucity of literature about the correlation of sleep quality (PSQI scores) with MoCA, GDS and CDR scores, although a weak linear correlation (coefficient of multiple correlation at 0.307-0.34) between sleep quality and GDS score was reported in Alzheimer's disease patients with moderate to severe dementia (CDR 2-3) 40 , indicating a possible connection of sleep disturbance with global deterioration scale at a late stage of AD patients.…”
Section: Discussionsupporting
confidence: 60%
“…Beneficial effect of gamma sensory stimulation on sleep quality in mild to moderate AD patients is particularly relevant, since scientific and clinical observations demonstrating a close relationship between sleep quality and activities of daily living (Zhou et al, 2019). It can be presumed that improving sleep quality in AD patients would provide multiple benefits: better sleep will enhance patients' daytime performance and reduce daytime sleepiness.…”
Section: Discussionmentioning
confidence: 99%
“…The SDI is a questionnaire that evaluates the severity and frequency of sleep-related problems derived from the NPI (insomnia, night roaming, daytime sleep, etc.). Zhou et al [34] have reported that higher PSQI total scores and scores of sleep latency from PSQI components in AD patients are associated with higher NPI total scores. Meanwhile, Cupidi et al [35] have analyzed scores of the seven components of the PSQI for caregivers of AD patients and found that their PSQI total scores and scores for two components (sleep latency and sleep disturbances) are significantly increased compared to those scores of controls.…”
Section: Discussionmentioning
confidence: 99%